Representasi Makna Pesan Panggilan Cinta Allah SWT dalam Syair Lagu Religi Surga Hati Karya Band Ungu - M. Yusuf; Nurul Rosita Dewi (El-Hikmah: Jurnal Ilmu Dakwah dan Komunikasi, 2015)
The purpose of this study was to determine the meaning of the message of love call Allah in Heaven song lyric Purple Heart Band works. This research method, semiotics of Ferdinand de Saussure thought that considered that the meaning can not be seen individually. Saussure also asserted that language is a social phenomenon, a language that is autonomous structure of the language is not a reflection of the structure of thought or reflection of the facts. In Saussure's theory explained that the sign has three interrelated elements, namely bookmarks (signifier), markers (signified) and its significance. In the study the lyrics of the song Heaven heart is separated into five stanzas, each stanza then analyzed with the semiotic theory of Sausure, there are three elements, namely bookmarks (signifier), markers (signified) and its significance. This process connects the meaning of the lyrics of a song with a message of love call of Allah. This interpretation is reinforced by taking reference from the book, website. The song Heaven Purple Heart Band work has meaning barkaitan the meaning of the message Call Love Allah.